The Purification of Islamic Education System in Risalat an-Nur Perspective: A Case Study in Malaysia: [Pemurnian Sistem Pendidikan Islam Berdasarkan Metode Risalah An-Nur: Analisis Kajian di Negara Malaysia] - Nurulwahidah Fauzi (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
Ethnocentric concepts, theories and practices in education, predominantly embedded in western philosophy and values, tend to ignore the growing multicultural nature of educational institutions. In contrast, Islamic education and learning is an important aspect to develop of quality human capital and human resources development. Malaysia as a country in Southeast Asia that is developing as one of the strategic determinant in the economic, social, cultural international politics and applying the "Asian Cultural Strategy Based on Islam”. However, in recent years, the study found that the moral values of young people today is significantly reduced, allowing the question to what extent education or tarbiyah aspect emphasized in learning today. Through an examination of the higher education sistems, the authors explore the problems and effectiveness of the education sistem that are practiced in the country to examine the appropriateness of the practice of Islamic education as the basic education. Secondly, to correct view of nature (worldview) on the Islamic Education in Malaysia and thirdly, propose a resolution to act in the direction to reform an Islamic education sistem based on the Risale An-Nur, the works of a mujaddid figure named Bediuzzaman Said Nursi. The authors conclude with (a) a discussion that Islamic education must cultivate a sense of identity within culture and community, while working with ancestral cultural knowledge retentions. This calls for a previsioning of the educational sistem in public schools so as to introduce a more effective method of teaching diverse youth, (b) create the need and importance of the Quran in the national Education and (c) help learners to build self-confidence in the collective defense of cultural identity in an increasingly challenging social environment on this day.[Konsep etnosentris, teori dan praktek di bidang pendidikan, terutama tertanam dalam filsafat Barat dan nilai-nilai, cenderung mengabaikan sifat multikultural pertumbuhan lembaga pendidikan. Sebaliknya, pendidikan dan pembelajaran Islam merupakan aspek penting untuk mengembangkan modal manusia dan pengembangan sumber daya manusia yang berkualitas. Malaysia, sebagai negara di Asia Tenggara, berkembang sebagai salah satu penentu strategis dalam ekonomi, sosial, politik internasional budaya dan menerapkan "Strategi Kebudayaan Asia Berdasarkan Islam" itu. Namun, dalam beberapa tahun terakhir, studi ini menemukan bahwa moral nilai-nilai orang muda saat ini berkurang secara signifikan, sehingga pertanyaan apa pendidikan tingkat atau aspek Tarbiyah ditekankan dalam pembelajaran hari ini. Melalui pemeriksaan sistem pendidikan tinggi, penulis mengeksplorasi masalah dan efektivitas sistem pendidikan yang dipraktekkan di negara itu untuk memeriksa kelayakan praktek pendidikan Islam sebagai pendidikan dasar. Kedua, untuk memperbaiki pandangan alam (pandangan dunia) pada Pendidikan Islam di Malaysia dan ketiga, mengusulkan resolusi untuk bertindak dalam arah reformasi sistem pendidikan Islam berdasarkan Risale An-Nur , karya-karya tokoh Mujaddid bernama Badiuzzaman Said Nursi. para penulis menyimpulkan dengan (a) diskusi bahwa pendidikan Islam harus menumbuhkan rasa identitas dalam budaya dan masyarakat, saat bekerja dengan leluhur retensi pengetahuan budaya. Ini panggilan untuk pre-visi dari sistem pendidikan di sekolah umum sehingga untuk memperkenalkan metode yang lebih efektif mengajar pemuda yang beragam, (b) membuat kebutuhan dan pentingnya Quran dalam Pendidikan nasional dan (c) bantuan peserta didik untuk membangun kepercayaan diri dalam pertahanan kolektif identitas budaya dalam lingkungan sosial yang semakin menantang pada hari ini.]